USHUL FIQH AS LEGAL EPISTEMOLOGY: BETWEEN TEXTUALITY AND RATIONALITY - Putri Rahyu; Nasrullah (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2026)
Ushul fiqh is the foundation of legal knowledge that lies between text and reason. The main focus of this research is to explain how ushul fiqh functions as a method of istinbath to address various new issues that arise in society. This research uses qualitative literature study. Furthermore, the secondary data collected were analyzed using descriptive analysis methods with a contextual approach. This study shows that the epistemology of ushul fiqh remains relevant and adaptive in facing various issues that develop over time due to the combination of revelation (textual) and reason (rational).